2020
DOI: 10.1002/chem.201905790
|View full text |Cite
|
Sign up to set email alerts
|

Structural Tunability and Diversity of Two‐Dimensional Lead Halide Benzenethiolate

Abstract: Two-dimensional (2D) organic-inorganic hybrid materials are currently of great interestf or applications in electronics and optoelectronics.H ere, the synthesis and optical properties of an ew type of halide-organothiolate-mixed 2D hybrid material, Pb 2 X(S-C 6 H 5 ) 3 ,a re reported, in which Xi s ah alide (I, Br,o rC l). Different from conventionall ead-based 2D layered materials, these compounds feature unusualf ivecoordinated lead centers with as tereochemically active electron lone pair on the lead atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…New types of functional organic building blocks, such as chiral molecules, organic radical species, organothiolate linkers, and photo-switchable and polymerizable species have yet been incorporated into the inorganic lattice. [83][84][85][86][87] Therefore, a clear research opportunity in this field is to bring the significant advances associated with organic chemistry into the hybrid perovskite world. While care must be taken to ensure that the molecular designs of the organic components do not interrupt the structure-directing function historically associated with organic ligands in hybrid perovskite structures, the creativity and nearly-endless design space associated with organic chemistry will allow for these types of efforts to occur.…”
Section: Discussionmentioning
confidence: 99%
“…New types of functional organic building blocks, such as chiral molecules, organic radical species, organothiolate linkers, and photo-switchable and polymerizable species have yet been incorporated into the inorganic lattice. [83][84][85][86][87] Therefore, a clear research opportunity in this field is to bring the significant advances associated with organic chemistry into the hybrid perovskite world. While care must be taken to ensure that the molecular designs of the organic components do not interrupt the structure-directing function historically associated with organic ligands in hybrid perovskite structures, the creativity and nearly-endless design space associated with organic chemistry will allow for these types of efforts to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Three thiol ligands are mainly investigated in this work, namely, methyl 4-mercaptobenzoate (MMBA), 4-(methylthio)­benzenethiol (MSBT), and 4-methoxybenzenethiol (MOBT) (Figure a). In addition, the unsubstituted benzenethiol (BT) ligand that forms 1D LOC is also included as the baseline for comparison. Some other thiol ligands have also been investigated as potential ligand candidates for 2D LOCs, but due to various factors (such as difficulty in single crystal synthesis, low-dimensional crystal structure, etc. ), they were not studied in detail (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The unsubstituted BT ligand results in a heavily hemidirected coordination with 4-coordinated lead connecting into a 1D chain, as reported in previous research (Figure 1c, Figure S8). 31 On the contrary, substitution on the phenyl ring of the organic ligands results in increased connectivity of the inorganic motif. Specifically, Pb(MMBA) 2 features 4-coordinated lead, organized in 8-member rings with sulfur atoms alternating below and above the basal plane of lead (Figure 1c, Figure S9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While perovskites containing small tail ligands such as butylammonium and phenylethyl­ammonium have had limited successes, perovskites containing longer chain π-conjugated ligands such as 2-(3‴,4′-dimethyl-[2,2′:5′,2″:5″,2‴-quater­thiophen]-5-yl)­ethan-1-aminium (4Tm) and 2-([2,2′-bithiophen]-5-yl)­ethan-1-aminium are more effective increasing light, temperature, and moisture stability. ,, It was found that treating 3D perovskite with 4Tm creates a 2D multifunctional capping layer which also assists the device performance and healing recovery in dark (Figure e) . Instead of converting PbI 2 into 2D-perovskite, lead–sulfur–halide compounds can be formed which are promising ion migration barriers, too. , In a halide perovskite and lead–chalcohalide nanocrystal heterostructure, only the perovskite domain halide converted to an alternative halide after an anion exchange reaction, which suggests inorganic crystals can also be effective ion migration barriers …”
Section: Understanding Degradation In Perovskite Solar Cellsmentioning
confidence: 99%
“…5 Instead of converting PbI 2 into 2D-perovskite, lead−sulfur−halide compounds can be formed which are promising ion migration barriers, too. 45,46 In a halide perovskite and lead−chalcohalide nanocrystal heterostructure, only the perovskite domain halide converted to an alternative halide after an anion exchange reaction, which suggests inorganic crystals can also be effective ion migration barriers. 45 2.2. fabricated in air and even with water incorporated directly in the precursor solution.…”
Section: Understanding Degradation In Perovskitementioning
confidence: 99%